1983
DOI: 10.1159/000238193
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Trimethoprim and Sulfadiazine into Sinus Secretion in Acute Maxillary Sinusitis

Abstract: The concentrations of trimethoprim (TMP), sulfadiazine (SD) and acetyl-SD in serum and maxillary sinus secretions of 10 patients with acute maxillary sinusitis were measured at the steady-state of continuous b.i.d. treatment with 160 mg of TMP + 500 mg of SD. The samples were collected 2–4 h after the preceding dose of TMP/SD. The mean TMP concentrations were 2.97 ± 0.35 µg/ml (mean + SE) and 3.85 ± 1.12 µg/ml in serum and sinus secretion, respectively. The average sinus secretion/serum ratio was 1.33. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1986
1986
1988
1988

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…The distribution in nasal secretions was studied by Ullmann et al (1983) who gave 1.0g co-trimazine to 20 healthy volunteers for 4 days. The AUC in nasal fluid was 140% of that in the serum in the case of sulphadiazine and 300% for trimethoprim, these values being similar to those reported by Mattila et al (1983). The concentrations present in nasal fluid exceeded the minimum inhibitory concentrations of the more commonly isolated respiratory tract pathogens throughout the dosage intervals.…”
Section: Distributionsupporting
confidence: 85%
“…The distribution in nasal secretions was studied by Ullmann et al (1983) who gave 1.0g co-trimazine to 20 healthy volunteers for 4 days. The AUC in nasal fluid was 140% of that in the serum in the case of sulphadiazine and 300% for trimethoprim, these values being similar to those reported by Mattila et al (1983). The concentrations present in nasal fluid exceeded the minimum inhibitory concentrations of the more commonly isolated respiratory tract pathogens throughout the dosage intervals.…”
Section: Distributionsupporting
confidence: 85%
“…Like several previous studies with other tissues, our findings confirmed that extravascular TMP concentration exceeds that simultaneously present in serum [7][8][9][10]. TMP levels now measured in bile were, however, considerably higher than those reported earlier [2], Although an avid lipid solubility of TMP is the basis for good tis sue penetrance, this does not entirely ac count for its accumulation in bile and gall bladder.…”
Section: Discussionsupporting
confidence: 89%
“…Salivary: serum trimethoprim ratios are 0.87 ± 0.2 (Watson & Stewart 1986); the sinus secretion: serum ratio is 1.33 for trimethoprim and 0.2 for sulphadiazine (Mattila et al 1983). Penetration of co-trimoxazole into breast milk is similar to that into saliva (Arnauld et al 1972), and into aqueous humour is 20% and 30%, respectively, of serum concentrations of trimethoprim and sulphamethoxazole (Salmon et al 1975).…”
Section: Distributionmentioning
confidence: 93%